2020
DOI: 10.1080/16549716.2020.1791426
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sexual and reproductive health among adolescents in Lao PDR

Abstract: Background: Adolescents are particularly vulnerable to poor sexual and reproductive health outcomes. In addition, Lao PDR has the highest teenage pregnancy rate in southeast Asia and a high maternal mortality ratio. Objective: This study aimed to provide a comprehensive exploration of factors that influence SRH knowledge, attitudes, and practices of adolescents in Bokeo Province, Lao PDR. Method: Data from the Adolescent Girl Situation Analysis cross-sectional study, collected in 2018 using a mixed-method appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…Other important findings in our study were significant differences in between the study districts which could possibly be explained by higher background education status among women in Vangvieng. Pregnant women in Feuang district were younger which is probably linked with a high number of early marriages in this area, where 61% of the population belongs to ethnic minority groups [ 39 , 40 ]. As indicated previously in the Lao PDR Social Indicator Survey most women in the Lao-Tai ethnic group live in urban areas and have higher literacy as compared to other ethnic groups [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other important findings in our study were significant differences in between the study districts which could possibly be explained by higher background education status among women in Vangvieng. Pregnant women in Feuang district were younger which is probably linked with a high number of early marriages in this area, where 61% of the population belongs to ethnic minority groups [ 39 , 40 ]. As indicated previously in the Lao PDR Social Indicator Survey most women in the Lao-Tai ethnic group live in urban areas and have higher literacy as compared to other ethnic groups [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first part collected background information (gender, age, educational qualification, marital status and religion) on the study participants. The decision to collect this information was based on a review of the literature [ 1 , 2 , 12 – 17 , 20 , 35 , 38 , 49 , 50 ] and recommendations from the GNAD and experts about appropriate information to collect from deaf persons.…”
Section: Method: Phasementioning
confidence: 99%
“…Most studies have reported that challenges such as lack of policies [ 28 , 29 ], low education levels [ 30 ], poverty [ 12 , 24 , 31 , 32 ], culture [ 33 , 34 ], stigma [ 8 , 16 ] and lack of parental support [ 14 , 35 ] contribute to the inability of girls and women to access SRH services. Other studies have also found that a high prevalence of teenage pregnancy is likely linked to factors such as poverty [ 12 , 25 ], illiteracy [ 30 , 36 – 38 ] and lack of awareness of contraceptive methods [ 15 ]. Furthermore, giving birth as a teenager has its own health and social drawbacks [ 37 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal as a method to prevent pregnancy was reported by 16.7% of our male respondents which is twice as high as that reported by a study conducted in Lao People's Democratic Republic. 29 The current study found low consensual partner serostatus disclosure among YPLHIV. Our findings are similar to those of other studies.…”
Section: Discussionmentioning
confidence: 44%